(untitled) (Management & Public Policies Journal, 2022)
The issue of migrants and refugees is carried out by organizations at a global level such as the United Nations (UN) as well as the WHO (World Health Organization). As they are groups of people who live in a situation of constant insecurity, with the arrival of the SARS-CoV-2 virus pandemic, attention is drawn to the impact on the lives of those people who, prior to the pandemic, already lived in precarious and even sub- human beings, falls heavily in view of the consequences brought by this new virus, both in health issues and in economic issues. This work presents an analysis of the immigration panorama from the international perspective, starting from covid-19, passing briefly on gender issues. The term “migrant” is also adopted in several passages of the text because it is a correct term, according to UNHCR (2015). Furthermore, it also analyzes the scenario before and after the pandemic in Brazil regarding the situation of migrants and refugees, both in terms of migratory flows and the labor market.